THE STUDY OF PROPERTIES OF SODA PRODUCTION WASTES AS ANTI-ICING REAGENTS - Oleksandr Suvorin; Inna Kravchenko; Maryna Ozheredova; Yevhen Zubtsov; Václav Píštěk (Environmental Problems, 2022)
The article considers the possibility of reducing the man-made load on surface and ground waters in Lysychansk-Severodonetsk industrial agglomeration caused by numerous sludge collectors and tailings storage facilities of various industries formed many decades ago. The paper providesinformation on the location and technical condition of the sludge collectors of the liquidated “LYSSODA”manufacture(Luhansk oblast), the amount of waste currently stored in them as well as the impact of these wastes on the quality of groundwater in the area where the sludge collectors are located. The work shows one of several possible options for using such wastes as a valuable secondary mineral raw material for obtaining a marketable product. The averaged data on the chemical composition of the solid phase of sludge and indicators of the liquid phase composition are given.According to the results of the analysis of scientific and technical information, it has been found that such wastes can ultimately be used for the production of anti-icing reagents. The obtained results of research on the dependence of the freezing point of working solutions on the concentration of salts, including the added corrosion inhibitors (triethanolamine, hexamethylenetetramine), indicate the feasibility of using soda ash production waste to obtain effective liquid anti-icing reagents without a mechanical component, while the optimal amount of added corrosion inhibitors is 0.5% wt. Such reagents can be used both undiluted at temperatures up to minus 20°C andstrengthened to 15–20% wt. by calcium chloride at temperatures up to minus 40°C with consumption on highways at the level of about 100 g/m2of the treated surface.